An analysis of the impact of potholes and waste over-break on the economics of a stope panel on a platinum mine - Tlhapi, Kabelo (My University, 2009)
In the Bushveld Complex, potholes provide challenges that have proven difficult for management to handle. The lack of innovative ways of solving the challenges provided an environment in which value destructive paradigms came into existence. There currently exists as a result, a paradigm in which tonnes, rather than quality tonnes (tonnes against a certain grade) are the main focus of mine management. In this paradigm has long existed a rule of thumb that dictated that a panel can remain economically viable with two-thirds of its facelength being offreef. This research employs a simple MS Office Excel-based model to investigate the impact of varying pothole size and primary contamination on the rule of thumb. A practical industry example is then used to show the impact on business, of the current paradigm. This research found that the amount of off-reef that a stope panel in a platinum mine can tolerate is largely dependent on the operation’s overall pay limit and that the off-reef tolerance decreases with increasing pay limit. For the particular mine that this research was carried out on, the findings are that the maximum offreef that a panel can mine is forty-two percent. Finally, based on the findings of this research, recommendations and additional areas of research are identified, which could help mine management in the platinum industry achieve a paradigm shift, as well as enhance the findings in this report.